Single-cell analysis reveals melanocytes may promote inflammation in chronic wounds through cathepsin G - Yakupu, Aobuliaximu; Zhang, Di; Guan, Haonan; Jiang, Minfei; Dong, Jiaoyun; Niu, Yiwen; Tang, Jiajun; Liu, Yingkai; Ma, Xian; Lu, Shuliang (Frontiers in Genetics, 2023)
During acute wound (AW) healing, a series of proper communications will occur between different epidermal cells at precise temporal stages to restore the integrity of the skin. However, it is still unclear what variation happened in epidermal cell interaction in the chronic wound environment. To provide new insights into chronic wound healing, we reconstructed the variations in the epidermal cell-cell communication network that occur in chronic wound healing via single-cell RNA-seq (scRNA-seq) data analysis. We found that the intricate cellular and molecular interactions increased in pressure ulcer (PU) compared to AW, especially the PARs signaling pathways were significantly upregulated. It shows that the PARs signaling pathways’ main source was melanocytes and the CTSG-F2RL1 ligand-receptor pairs were its main contributor. Cathepsin G (CatG or CTSG) is a serine protease mainly with trypsin- and chymotrypsin-like specificity. It is synthesized and secreted by some immune or non-immune cells. Whereas, it has not been reported that melanocytes can synthesize and secrete the CTSG. F2R Like Trypsin Receptor 1 (F2RL1) is a member of proteinase-activated receptors (PARs) that are irreversibly activated by proteolytic cleavage and its stimulation can promote inflammation and inflammatory cell infiltration. In this study, we found that melanocytes increased in pressure ulcers, melanocytes can synthesize and secrete the CTSG and may promote inflammation in chronic wounds through CTSG-F2RL1 pairs, which may be a novel potential target and a therapeutic strategy in the treatment of chronic wounds.